Targeted 5-fluorouracil-1-acetic acid delivery utilising cell penetrating peptide conjugated hepatitis b virus-like nanoparticles to squamous cell carcinoma A431 - Gan, Bee Koon (2020)
Skin cancer is a prominent global public health problem with no signs of plateauing in its incidence. As the most common treatments for skin cancer, surgical resection inevitably damages a patient's appearance, and chemotherapy has many side effects. Thus, the main goal of the study was to screen for a cell penetrating peptide (CPP) for the development of a targeting drug delivery system applying truncated hepatitis B core antigen (tHBcAg) virus-like nanoparticles (VLNPs) for skin cancer. With the application of biopanning utilizing Ph.D.™-12 Phage Display Peptide Library, a CPP with the sequence NRPDSAQFWLHH that specifically targets the human squamous carcinoma A431 cells was identified. The uptake of the CPP by A431 cells is an energy dependent process, and the CPP was proven to enter the A431 cells via the interaction with epidermal growth factor receptor (EGFR), a transmembrane protein that is involved in cell signaling pathways that control cell division and survival. Methyl-β-cyclodextrin (MβCD) and chlorpromazine hydrochloride (CPZ) inhibited the internalisation of the CPP into the A431 cells, suggesting the peptide entered the cells via clathrin-dependent endocytosis. To conjugate the CPP to tHBcAg VLNPs, the CPP was cosynthesised with peptide SLLGRMKGA (the nanoglue) at its C-terminus, and these sequences were separated by a linker (GGG). The resulting 24-residue peptide, NRPDSAQFWLHHGGG-SLLGRMKGA, was directly coupled covalently to the spikes of the tHBcAg VLNPs via carboxylate groups using the zero length cross-linker EDC and Sulfo-NHS. The CPP displayed on hepatitis B virus-like nanoparticles (VLNPs) via the nanoglue successfully delivered the nanoparticles into A431 cells. The CPP conjugated tHBcAg VLNPs (CPP-tHBcAg VLNPs) were further conjugated with 5-fluorouracil-1-acetic acid (5-FA) via the primary amine groups on the surface of tHBcAg VLNPs using Sulfo-NHS/EDC as the targeting ligand for cancer chemotherapy. Transmission electron microscopy showed that the tHBcAg VLNPs maintained their integrity after the conjugation of the CPP and 5-FA on their surfaces. Approximately 833 5-FA molecules were conjugated covalently to each CPP-tHBcAg VLNP. 5-FA is the derivative of 5-fluorouracil (5-FU) which is less toxic but with enhanced cytotoxicity once it was coupled covalently to the CPP conjugated tHBcAg VLNPs. Furthermore, the targeting property of the CPP resulted in selective cytotoxicity of the 5-FA-CPP-tHBcAg VLNPs in EGFR-dependent manner. The MTT assay indicated that tHBcAg VLNPs conjugated with CPP and 5- FA significantly increased the cytotoxicity of 5-FA in A431 cells, which expressed the highest level of EGFR (2.14 folds) as compared with that of free 5-FU. The cytotoxicity of 5-FA-CPP-tHBcAg VLNPs was reduced in HT29 cells and HeLa cells, which have a lower number of EGFR per cell. This demonstrated that the CPP is a potential ligand for targeted delivery of VLNPs into skin cancer cells and other cancer cells, which overexpress epithelial growth factor receptor (EGFR). This paves the way to deliver drugs, nucleic acids and molecules into cells overexpressing EGFR. The application of this peptide is not restricted as a ligand to target and internalise VLNPs into cells, it can also be incorporated into other nanoparticles for a wider application in nanomedicine and targeting cancer imaging. In addition, the newly established drug delivery systems demonstrated that the tHBcAg VLNP is a potential nano-vehicle in chemotherapeutics to target various cells specifically by displaying different cell specific ligands at the tips of tHBcAg VLNPs.